Economic development finance - Seidman, Karl F. (Sage Publications, 2005)
Economic Development Finance is a comprehensive and in-depth presentation of private, public, and community financial institutions, policies and methods for financing local and regional economic development projects. The treatment of policies and program models emphasizes their applications and impact, key design and management issues, and best practices. A separate section addresses critical management issues for development finance programs: program and product design, the lending and investment process, and capital management. Case studies are included throughout the book to help readers develop their skills and apply policies and tools to real practice issues. A glossary of finance terms is also included. Economic Development Finance provides a foundation for students and professionals in the technical aspects of business and real estate finance and surveys the full range of policies, program models, and financing tools used in economic development practice within the United States.